Optimization of fiber scintillator detector system for use in monitoring small animal arterial input function - Rubena Yusoff; Khadizah Ghazali; Norini Tahir; Fatihah Anas Muhiddin; Mohamed Rafiq Ghazali; Jumat Sulaiman (Universiti Malaysia Sabah press, 2024)
Monitoring small animal arterial input function using spectrometry poses significant challenges due to the high gamma background radiation, which makes the application of standard spectrometric methods nearly impossible. In response to this issue, a fiber scintillator detector prototype was developed in this study to optimize and facilitate local, real-time measurements under such challenging conditions. The prototype consists of five plastic scintillating fibers, each measuring 50 mm in length and 250 µm in diameter. These fibers are coupled to a 1 x 1 mm Silicon Photomultiplier (SiPM), all encased within a custom-made aluminum housing. This design was intended to optimize the detector's ability to accurately measure radiation in environments with significant gamma interference. The microprobe was immersed in a vial containing a homogeneous aqueous solution of 18F for a duration of 240 minutes. The system demonstrated effective gamma/beta discrimination, which is crucial for accurate spectrometric analysis in environments with mixed radiation types. The prototype also exhibited an absolute sensitivity of 500 counts per second (cps) per MBq per milliliter, indicating its efficiency in detecting radiation at low concentrations. Furthermore, the decay time measurements revealed only a ~2.5% deviation from the actual value, showcasing the system's precision. These findings suggest that the developed probe is a promising tool for quantitative measurement in various applications, particularly in scenarios where traditional spectrometric methods fail due to high gamma backgrounds. Its ability to deliver real-time, local measurements with high sensitivity and accuracy could pave the way for advancements in small animal studies and other fields requiring precise radiation detection.